Pan-TRK immunohistochemistry in gynaecological mesenchymal tumours: diagnostic implications and pitfalls - Moura, Madalena Souto; Costa, João; Velasco, Valérie; Kommoss, Felix; Oliva, Esther; Le Loarer, Francois; McCluggage, W Glenn; Razack, Rubina; Treilleux, Isabelle; Mills, Anne; Longacre, Teri A.; Devouassoux-Shisheboran, Mojgan; et al. (Histopathology, 2024)
Aims NTRK-rearranged sarcomas of the female genital tract mainly occur in the uterus (more commonly cervix than corpus) and are characterized by a “fibrosarcoma-like” morphology and NTRK gene rearrangements. These neoplasms may exhibit histological overlap with other entities and can present diagnostic difficulties without molecular confirmation. Pan-TRK immunohistochemistry was developed to identify tumours harbouring NTRK rearrangements. The aim of this study was to characterize pan-TRK immunohistochemical expression in a large cohort of gynaecological mesenchymal neoplasms and investigate the utility of pan-TRK immunohistochemistry to distinguish NTRK-rearranged sarcoma from its mimics. Methods and results A total of 473 gynaecological mesenchymal tumours (461 without known NTRK fusions and 12 NTRK-rearranged sarcomas) were selected. Pan-TRK immunohistochemistry (EPR17341, Abcam) was performed on whole tissue sections and tissue microarrays. Molecular interrogation of pan-TRK positive tumours was performed by RNA sequencing or fluorescence in situ hybridization (FISH). Of the 12 NTRK-rearranged sarcomas, 11 (92%) exhibited diffuse (≥70%) cytoplasmic pan-TRK staining with moderate/marked intensity, while the other was negative. Eleven (2.4%) additional tumours also exhibited pan-TRK immunohistochemical expression: three low-grade endometrial stromal sarcomas, seven high-grade endometrial stromal sarcomas, and an undifferentiated uterine sarcoma. Molecular confirmation of the absence of NTRK rearrangements was possible in nine of these tumours. Of these nine neoplasms, seven exhibited focal/multifocal (<70%) pan-TRK cytoplasmic staining with weak/moderate intensity. Conclusion Even though pan-TRK immunohistochemical expression is not entirely sensitive or specific for NTRK-rearranged sarcomas, these neoplasms tend to exhibit diffuse staining of moderate/strong intensity, unlike its mimics. Pan-TRK should be performed in monomorphic uterine (corpus and cervix) spindle cell neoplasms that are negative for smooth muscle markers and hormone receptors and positive for CD34 and/ or S100. Ultimately, the diagnosis requires molecular confirmation.
Online veröffentlicht am 21. November 2023
Gesehen am 22.04.2024